Instructional Quality Questionnaire: Development of Instructional Quality Measurement Tools for Secondary Education Teachers - Megah Syifa Rinjani Sujarko; Airin Triwahyuni (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Instructional quality is a form of classroom teaching which is important to support the development of students’ abilities in class. Instructional quality has three dimensions, that is a collection of teachers’ teaching behaviors, namely classroom management, supportive climate, and cognitive activation. Measurements of instructional quality has begun to develop; however, no measurement scale has been constructed and used in Indonesia. This study discussed the adaptation of Instructional Quality Questionnaire with the aim of obtaining a measurement for instructional quality that is standardized and can be used in Indonesian population. The adaptation process carried out includes pre-condition stage, development stage and confirmation stage. A tryout of the instrument is carried out on 242 high school students. The final instructional quality scale consists of 18 items which measure all three dimensions with reliability (r=0,886) which indicates that the instrument is reliable. Collection of internal structure validity using confirmatory factor analysis shows that the validity construct of the instructional quality model is a good fit. This adaptation of instrument is expected to help the development of research related to instructional quality as an important construct in determining the increase in students’ abilities and achievements, especially in Indonesia. Meanwhile, the construction of the items that is flexible to be used in any population and context is expected to facilitate the needs of various research.Instructional quality atau kualitas instruksional guru merupakan bentuk dari classroom teaching yang penting untuk mendukung perkembangan kemampuan siswa di kelas. Instructional quality memiliki tiga dimensi berupa kumpulan perilaku guru ketika mengajar yaitu classroom management, supportive climate dan cognitive activation. Pengukuran kualitas instruksional telah mulai dikembangkan namun belum terdapat skala pengukuran yang telah dikonstruksikan dan digunakan di Indonesia. Penelitian ini membahas mengenai adaptasi Instructional Quality Questionnaire dengan tujuan untuk mendapatkan alat ukur instructional quality yang dapat digunakan pada populasi di Indonesia yang terstandarisasi. Proses adaptasi yang dilakukan meliputi tahap pre-kondisi, pengembangan dan konfirmasi. Uji coba alat ukur dilakukan kepada 242 siswa SMA/SMK/sederajat. Alat ukur final instructional quality terdiri dari 18 item yang mengukur ketiga dimensinya dengan reliabilitas (r=0,886) yang mengindikasikan alat ukur reliabel. Pengumpulan bukti validitas struktur internal dengan menggunakan confirmatory factor analysis menunjukkan bahwa model instructional quality memiliki hasil validitas konstruk baik (good fit). Pengembangan terhadap alat ukur instructional quality ini diharapkan dapat membantu perkembangan penelitian terkait konstruk perilaku instruksional sebagai konstruk yang penting dalam menentukan peningkatan kemampuan dan pencapaian siswa khususnya di Indonesia. Penyusunan item alat ukur yang fleksibel untuk dapat digunakan pada berbagai populasi dan konteks juga diharapkan dapat memfasilitasi kebutuhan beragam tujuan penelitian.